Road safety problems associated with increased use of e-powered personal mobility vehicles. Kaunas city case study - Zagorskas, Jurgis; Damidavičius, Jonas (International Conference “Environmental Engineering”, 2020)
Increased use of e-powered personal mobility vehicles is usually considered as a positive change; it is generally agreed that Personal Mobility Vehicles (PMVs) effectively and efficiently reduce negative environmental impacts of transport and improve the quality of life. There has been great technological progress made by all sectors in the field of personal mobility during the last decade. Use of PMV for micro-mobility is welcomed by market, consumers and governments and thus it is becoming increasingly popular in modern European society. New technology driven PMVs bring opportunities to their users, but at the same time create problems with street space sharing, road safety and traffic offenses. This study gives an overview of recent types of PMVs, offers some insights into the upcoming changes and challenges, and raises the discussion on themes related with increased use of e-powered personal transporters.